PENGARUH FOREIGN DIRECT INVESTMENT, REMITANSI, KREDIT, KETERBUKAAN PERDAGANGAN DAN PENGELUARAN KONSUMSI PEMERINTAH TERHADAP PDB ASEAN - Fitria Sari; Taufiq C Dawood (Jurnal Ilmiah Mahasiswa Ekonomi Pembangunan, 2022)
Abstract This study aims to analyze the effect of foreign direct investment (FDI), remittances, bank credit, trade openness and government final consumption expenditure of GDP in ASEAN in the period 1990 to 2017 using the fixed effect model (FEM). The result of this study indicate that simultaneous FDI, remittances, bank credit, trade openness and government final consumption expenditure have a positive and statistically significant effect on GDP in ASEAN. Keywords: Foreign direct investment (FDI), remittances, bank credit, trade openness, government, final                      consumption expenditure.